Impact of ozone exposure on the phagocytic activity of human surfactant protein A (SP-A) and SP-A variants - Mikerov, Anatoly N. (2007)
Surfactant protein A (SP-A) enhances phagocytosis of Pseudomonas aeruginosa. SP-A1 and SP-A2 encode human (h) SP-A; SP-A2 products enhance phagocytosis more than SP-A1. Oxidation can affect SP-A function. We hypothesized that in vivo and in vitro ozone-induced oxidation of SP-A (as assessed by its carbonylation level) negatively affects its function in phagocytosis (as assessed by bacteria cell association). To test this, we used P. aeruginosa, rat alveolar macrophages (AMs), hSP-As with varying levels of in vivo (natural) oxidation, and ozone-exposed SP-A2 (1A, 1A(0)) and SP-A1 (6A(2), 6A(4)) variants. SP-A oxidation levels (carbonylation) were measured; AMs were incubated with bacteria in the presence of SP-A, and the phagocytic index was calculated. We found: 1) the phagocytic activity of hSP-A is reduced with increasing levels of in vivo SP-A carbonylation; 2) in vitro ozone exposure of hSP-A decreases its function in a dose-dependent manner as well as its ability to enhance phagocytosis of either gram-negative or gram-positive bacteria; 3) the activity of both SP-A1 and SP-A2 decreases in response to in vitro ozone exposure of proteins with SP-A2 being affected more than SP-A1. We conclude that both in vivo and in vitro oxidative modifications of SP-A by carbonylation reduce its ability to enhance phagocytosis of bacteria and that the activity of SP-A2 is affected more by in vitro ozone-induced oxidation. We speculate that functional differences between SP-A1 and SP-A2 exist in vivo and that the redox status of the lung microenvironment differentially affects function of SP-A1 and SP-A2.